2017
DOI: 10.1038/nature24636
|View full text |Cite
|
Sign up to set email alerts
|

Fully integrated silicon probes for high-density recording of neural activity

Abstract: Summary Paragraph Sensory, motor, and cognitive operations involve the coordinated action of large neuronal populations across multiple brain regions in both superficial and deep structures1,2. Existing extracellular probes record neural activity with excellent spatial and temporal (sub-millisecond) resolution but from only a few dozen neurons per shank. Optical Ca2+ imaging3–5 offers more coverage but lacks the temporal resolution to reliably distinguish individual spikes and does not measure local field pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
1,772
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,808 publications
(1,793 citation statements)
references
References 32 publications
14
1,772
5
2
Order By: Relevance
“…54 Due to the technical challenges of in vivo intracellular patch clamp that is only applicable to acute recordings in anesthetized animals, 55,56 most intracerebral electrophysiology studies employ single-neuron level extracellular monitoring of neuronal activity with a focus on improving chronic stability 33 and increasing the throughput of simultaneously measured neurons. 7,32 …”
Section: Mesh Electronics Stably Monitors Brain Activity At the Singlmentioning
confidence: 99%
See 2 more Smart Citations
“…54 Due to the technical challenges of in vivo intracellular patch clamp that is only applicable to acute recordings in anesthetized animals, 55,56 most intracerebral electrophysiology studies employ single-neuron level extracellular monitoring of neuronal activity with a focus on improving chronic stability 33 and increasing the throughput of simultaneously measured neurons. 7,32 …”
Section: Mesh Electronics Stably Monitors Brain Activity At the Singlmentioning
confidence: 99%
“…31 The external region with I/O pads is injected onto a thin polymer film that allows direct ‘by-hand’ insertion and clamping of the I/O pads into a ZIF connector pre-mounted on a printed circuit board (PCB, Figure 3B). The PCB is fixed onto the animal’s skull as a compact and low mass interface (1.3 g and 0.65 g, with and without the detachable amplifier connected, respectively, 32 compared to at least 3 g for Michigan array silicon probes 7,57 ) for removable attachment of measurement electronics during chronic recording from awake restrained or free-moving animals (Figure 3C). In addition to facilitating adoption of the mesh electronics by nonexpert laboratories, the plug-and-play interface has also enabled implementation of sterilization protocols necessary for human surgical environments.…”
Section: Mesh Electronics Stably Monitors Brain Activity At the Singlmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that probes based on TiN performed as well as those made of conventional materials when implanted in animals for 8 weeks. What's more, sites made of TiN are compatible with the CMOS processing, ensuring scalable fabrication of the Neuropixels probes at low cost [6].…”
mentioning
confidence: 99%
“…To meet this challenge, Jun and colleagues [6] have developed a silicon based probe called Neuropixels containing 960 sites on a single shank, which can simultaneously record the activity of more than 200 individual neurons. What's more, the length of the recording shank as long as 10 mm enables recording from multiple brain regions simultaneously, and even the deepest structures of a mouse brain can be accessed.…”
mentioning
confidence: 99%